(untitled) - Kingston, Jeffrey H. (Harlow, England, 1998)
This book provides a look at the central algorithms and data structures of computer science, together with an introduction to the techniques of design, correctness and analysis required for understanding them.
Phân tích và thiết kế thuật toán
Keywords: Thuật toán máy tính,Computer algorithms